Nonlinear static and dynamic analysis of composite layered plates and shells using finite strip methods - Razzaq, Raja Javed (Cranfield University, 2003)
In this thesis, a new concept of finite strip elements is introduced. Lagrangian, Hermitian and spline-type interpolations have been used independently along the two axes of the plate mid-plane. Different plate-bending theories; Mindlin, Reissner and Kirchhoff theories have been applied in the derivations of the new finitestrip elements, for isotropic and composite materials. The new elements have also been extended to work as faceted shell elements for the analysis of cylindrical shells, folded plates and stiffened plates. An efficient modular programming package based on those elements was designed, and it is capable of performing linear and non-linear stress analysis, buckling analysis and natural frequency analysis. The modular package, which was coded in FORTRAN has different solvers and a built-in mesh generator for different types of plate structures. A number of case studies have been employed for the validation of the package and testing its different capabilities. The package has proved to be an efficient tool for numerical modelling of plates, cylindrical shells, folded plates and stiffened plates made of isotropic and composite layered materials.